Wizualizacja dzieł romantycznych. Z polskich i czeskich doświadczeń filmowych - Dabert, Dobrochna (Slavia Occidentalis, 2011)
The text constitutes an attempt at a comparative analysis of the adaptations of the chosen romantic masterpieces. The works that have been subject to the analysis are the following: Dziady (Forefathers’ Eve) and Pan Tadeusz by Adam Mickiewicz, Kytice by Karl Jaromir Erben and Máj by Karel Hynek Mácha. The reflection on the adaptations of Polish and Czech romantic masterpieces in the exemplary form shows the scope of the adaptation strategies in the modern cinema. The erudite character of the adaptations by Tadeusz Konwicki, requiring a great knowledge of the literary work itself, but also a deep knowledge of the historiographic context of Polish Romanticism, became a task that brought artistic and intellectual satisfaction to few people. The trivialization of the works of Macha and Erben was rebuffed by the Czech literary scholars, though simultaneously accepted by the mass viewership which led to a box-office success. An intermediate position is taken up by Wajda’s Pan Tadeusz which balances on a thin border between artistic truth and a beautiful but empty effect.